IMPLEMENTASI ALGORITMA APPROXIMATE STRING MATCHING PADA APLIKASI FILOSOFI BERBASIS ANDROID - Nasution, Elvi Sahara; Hasibuan, Nelly Astuti; Suginam, Suginam (STMIK Budi Darma, 2018)
Philosophy is a critical thinking framework to find solutions to all problems. The solution found to overcome a problem through critical thinking is the fruit of philosophical thinking. If the solution to a problem is not thought out carefully and critically, then it is not the fruit of philosophical thinking but only the sound. Philosophy is useful to achieve a better life, especially in a job so that you can understand the reason why the order in a job must be carried out. In understanding philosophical terms generally use foreign-language scholarship because the term philosophy is the absorption word from English, namely philosophy. While the word philosophy itself is an absorption word from the Greek language. In Greek the combination of the word philo means love and sophÃ³s, which means wisdom makes a special word, philosophia, which means love wisdom. To learn the term philosophy is very difficult, especially for ordinary people. Based on this research the author designed the Android-based Philosophy application using eclipse juno and sqlite as the database. To facilitate the search process the meaning of philosophical terms in the application the author applies the Approximate string matching algorithm. Approximate algorithm (Estimated string matching) is a problem in computer science that is applied in text search, pattern recognition and signal processing applications. For the text T [1..n] and the pattern P [1 ... m], we are expected to find all occurrences of the pattern in the text with the most edit distance is K. The edit distance between two strings is defined as the minimum number of character insertions, deletions and the replacement needed to make it the same. The results expected in this study is an application that implements the Approximate Algorithm so that the process of searching quickly in the application can help the user to more easily understand philosophical terms.Keywords: Application Philosophy, Android, String Matching, Approximate Algorithm.